Preparation, Characterization and Application of the Delivery System for Food Products - Shuai Chen; Qing Guo (Foods, 2023)
In the dynamic and evolving landscape of food science and technology, the quest to develop innovative and effective delivery systems for bioactive compounds remains a focal point of research and development [...]